If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -1 = x + -7 Reorder the terms: -1 + 2y = x + -7 Reorder the terms: -1 + 2y = -7 + x Solving -1 + 2y = -7 + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2y = -7 + 1 + x Combine like terms: -1 + 1 = 0 0 + 2y = -7 + 1 + x 2y = -7 + 1 + x Combine like terms: -7 + 1 = -6 2y = -6 + x Divide each side by '2'. y = -3 + 0.5x Simplifying y = -3 + 0.5x
| 4y=y+14 | | 5-8x=3+4x | | 3z-6=z-8 | | 9x-18=-20 | | 9z=5z+10 | | 4(6-3n)=96 | | 4y+7=3y+9graph | | 3+4x=8-5x | | 28+20x=-44 | | 12x+8=4x-12 | | 11a+2b+2c=200 | | 2p-4=9+2p | | 2p-4=9-2p | | 32=9a+3b+c | | 3y+4=7y+9 | | 2a-b=ac | | 4x+-8+12=-40 | | 8x+10=10X | | Y^2-3x-10=0 | | 40t+45= | | v=(3.14)(4)2 | | b=(3.14)(14)2 | | 4x-2(4-6)=-40 | | b=(3.14)(4)2 | | -2n-8(n-3)=84 | | x+21=2x+30 | | n+9=4-6 | | 3+3x^2-16x^3=0 | | y^4-13y^3+36=0 | | 5(z+6)=82z | | x+(x*.15)=6.88 | | 10(s-4)=-105 |